1987
DOI: 10.1111/j.1365-246x.1987.tb05229.x
|View full text |Cite
|
Sign up to set email alerts
|

Microearthquakes in the TDP swarm, Turkey: clustering in space and time

Abstract: The third occupation (experiment TDP3) of recording sites above a persistent swarm of microearthquakes near the North Anatolian Fault, with a larger seismic network and over a longer period of time, confirms and refines previous observations with greater resolution. The greater resolution in earthquake locations has revealed marked clustering in time and space. Many, perhaps most, of the earthquakes belong to clusters, where successive earthquakes originate in a very small volume and have similar fault mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Although the Kandilli Observatory, Bogaziçi University, has established the MAR-NET seismic network for microearthquake observations (Ü çer et al, 1985), this network could not cover the whole seismic gap region. According to previous studies, microearthquake activity in the seismic gap region has been very low in general, except for some swarm areas (Crampin et al, 1985;Evans et al, 1987;Tsukuda et al, 1988;Lovell et al, 1989;Nishigami et al, 1990;Iio et al, 1991), but detailed characteristics have not been very clear without a dense network covering the seismic gap region.…”
Section: Introductionmentioning
confidence: 94%
“…Although the Kandilli Observatory, Bogaziçi University, has established the MAR-NET seismic network for microearthquake observations (Ü çer et al, 1985), this network could not cover the whole seismic gap region. According to previous studies, microearthquake activity in the seismic gap region has been very low in general, except for some swarm areas (Crampin et al, 1985;Evans et al, 1987;Tsukuda et al, 1988;Lovell et al, 1989;Nishigami et al, 1990;Iio et al, 1991), but detailed characteristics have not been very clear without a dense network covering the seismic gap region.…”
Section: Introductionmentioning
confidence: 94%
“…It has been well known that seismicity in the northern branch is rather high, as characterized by clustering of small earthquakes in some areas Evans et al, 1987;Lovell et al, 1989). In contrast, seismicity has been extremely low in the southern branch (Tsukuda et al, 1988;Nishigami et al, 1990;Iio et al, 1991).…”
Section: Seismicity Before the Mainshockmentioning
confidence: 99%
“…Crampin have shown that the parallel polarizations of the first split shear-waves can be consistently interpreted in terms of propagation through a distribution of vertical liquid-filled cracks aligned approximately N 100°E. This orientation is consistent with cracks opening normal to the approximately north-south axis of minimum compression, which has been identified from fault-plane solutions Crampin & Evans 1986;Lovell et al 1987). Shear waves which propagate through such a system of approximately east-west oriented vertical cracks will split and, at angles of incidence within the shear-wave window, the first-arriving (faster) split shear-wave will be polarized in the N 100°E plane of the cracks .…”
Section: Crack-induced Anisotropymentioning
confidence: 56%